Teaching Research in Design : Guidelines for Integrating Scientific Standards in Design Education - Dittenberger, Sandra (Design ;, 2022)
Since the 1990s, the concern to define areas of research in design has dominated academic debates. As a result, we are now facing a multitude of understandings. This is especially true for practice-based design research. Sandra Dittenberger, Hans Stefan Moritsch and Agnes Raschauer discuss how the concept of learning by research can be integrated into product design studio teaching. They show different international approaches for integrating research into teaching and contrast the areas of design research with scientific standards. The book features study results that helped generate both a general orientation for research in design education and guidelines for students of how to integrate research into their project work.